EDUKASI DAN PEMBERDAYAAN KELUARGA DALAM MENINGKATKAN PERILAKU HIDUP BERSIH DAN SEHAT TERHADAP STATUS GIZI BALITA DI WILAYAH PUSKESMAS BAITURRAHMAN BANDA ACEH - Muna, Sirajul; Aryani, Roza (LPPM Universitas Bina Bangsa, 2024)
One of the factors that influences the nutritional status of toddlers is clean and healthy living behavior. PHBS is a behavior that must be carried out consciously by a family. Poor PHBS can have an impact on the nutritional status of toddlers. Data obtained from the Banda Aceh City Health Service, in 2022, the number of toddlers weighed was 29,085 and those experiencing malnutrition were 2,209 (7.6%). The highest number of toddlers experiencing malnutrition was at the Baiturrahman Community Health Center at 27.6%, the Ulee Kareng Community Health Center at 26.3% and the Lampaseh Community Health Center at 26%. Clean and healthy living behavior has a big influence on the growth and development of toddlers, including their nutritional status, where the family plays a role in parenting and maintaining health so that toddlers avoid infectious diseases that can disrupt their growth and development